The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep28036
|View full text |Cite
|
Sign up to set email alerts
|

Serum GDF-8 levels change dynamically during controlled ovarian hyperstimulation in patients undergoing IVF/ICSI-ET

Abstract: Growth differentiation factor-8 (GDF-8) is found in the human serum, follicular fluid and granulosa cells. Our previous studies have shown that the human cumulus expansion and steroidogenesis can be regulated by GDF-8. However, thus far, the expression profile of GDF-8 in serum and whether the level of serum GDF-8 influences pregnancy results for patients treated with in vitro fertilization/intracytoplasmic sperm injection-embryo transfer (IVF/ICSI-ET) is totally unknown. In this study, we showed that GDF-8 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…We and other groups have shown that GDF-8 and its receptors are expressed in human granulosa cells. In addition, secreted GDF-8 has been detected in human ovarian follicular fluid [10][11][12][13]. Functionally, we have demonstrated that granulosa cell proliferation, steroidogenesis, cumulus expansion, and oocyte maturation are regulated by GDF-8 [11][12][13][14][15][16][17].…”
Section: Ivyspringmentioning
confidence: 82%
“…We and other groups have shown that GDF-8 and its receptors are expressed in human granulosa cells. In addition, secreted GDF-8 has been detected in human ovarian follicular fluid [10][11][12][13]. Functionally, we have demonstrated that granulosa cell proliferation, steroidogenesis, cumulus expansion, and oocyte maturation are regulated by GDF-8 [11][12][13][14][15][16][17].…”
Section: Ivyspringmentioning
confidence: 82%
“…Specifically, GDF8 regulates steroid production by increasing aromatase/estradiol production while decreasing StAR/progesterone production in primary hGL cells (Chang et al ., 2016b). Analysis of the data from clinical samples supports these findings, as there is a negative correlation between GDF8 concentrations and progesterone concentrations in the serum and follicular fluid (Fang et al ., 2015, 2016b). Moreover, GDF8 may enhance the FSH-induced aromatase/estradiol production, whereas GDF8 suppresses the LH-induced StAR/progesterone production in hGL cells (Chang et al ., 2016b).…”
Section: Novel Role Of Gdf8 In the Human Ovarymentioning
confidence: 99%
“…Interestingly, Fang et al. ( 42 ) found the serum concentration of GDF-8 to change dynamically in patients undergoing controlled ovarian hyperstimulation (COH) during IVF treatment ( Figure 1A ). Blood samples from 19 patients undergoing COH were assayed at seven time points: GnRH-a day; Gonadotropin (Gn) day; human chorionic gonadotropin (hCG) day; 12 h after hCG administration; OPU day; 48 h after OPU day; and 14 days after embryo transfer (ET).…”
Section: Expression Of Gdf-8 and Its Functional Receptors In The Huma...mentioning
confidence: 99%
“…GDF-8 may have an inhibitory role in regulation of progesterone production in the human ovary. Data from two studies ( 37 , 42 ). involving 31 infertile women undergoing IVF procedures indicated GDF-8 expression to be negatively correlated with the progesterone level in serum and follicular fluid.…”
Section: Expression Of Gdf-8 and Its Functional Receptors In The Huma...mentioning
confidence: 99%
See 1 more Smart Citation